Building community capacity for tourism development (CABI, 2008)
This book seeks to improve an understanding of what happens when communities turn to, or are subjected to, tourism as a development strategy; use this knowledge to change the process of tourism planning and development in ways that will lead to improved outcomes for destination residents; address some of the knowledge gaps and to further develop some aspects of building community capacity to help better manage and to better benefit from tourism development; and focus on what does and/or should happen in a community before any tourism development is initiated. Destination residents or communities are defined as persons and public and private bodies who are potentially affected, both positively and negatively, by the impacts of tourism development within the boundaries of the destination area. Much of the material in this book is based on studies of communities that often have low levels of tourism development. The book includes cases and examples from remote areas in Australia, including indigenous communities, regional destinations in Asia, emerging destinations in Africa, remote areas of South America, countries in the South Pacific and less-developed tourism destinations and sectors in the USA and Australia. The book consists of 11 chapters which are presented in three parts: improving knowledge of tourism development and its impacts; improving community knowledge of tourism development; and improving community participation in tourism development. Chapter 1 examines community capacity building as a precondition for any activity including tourism development, and only if tourism development is chosen as an option for community development. Chapter 2 examines some of the ways in which both tourists and tourism enterprises create economic costs and benefits within rural communities; and use that information to identify 'pathways' and 'pitfalls' for planners who are keen to enhance the net community benefits of this important regional industry. Chapter 3 provides a framework for understanding and benefiting from tourism's socio-cultural impacts by initially paying attention to cultural relativism, language use, social networks and the concept of well-being. Chapter 4 focuses on how ecotourism tour operators can work with communities to improve resident awareness and understanding of tourism impacts; it also offers suggestions for incorporating such activities into sustainability indicators and accreditation schemes. Chapter 5 examines criteria and steps towards community-based tourism (CBT) development to guide the development of more effective community tourism in Asia. Chapter 6 explores different techniques for enhancing community understanding of tourism encompassing a local and a 'Western' perspective as well as the host-guest relationship; and provides opportunities for partners in CBT development to understand the community's perspective. Chapter 7 discusses a new approach and framework in sustainable tourism and associated ecotourism development. Chapter 8 discusses the use of effective partnerships to increase various forms of capital available for development. Chapter 9 examines how tourism can open doors for women in keeping with the MDG to combat global poverty and hunger in marginal areas of developing countries that are dominated by women with no other forms of livelihood. Chapter 10 outlines the role of entrepreneurs in tourism, differentiates types of entrepreneurs, summarizes the methods for measuring entrepreneurial activity, discusses the climate needed for entrepreneurs to succeed and proposes an agenda for future research in the area of entrepreneurship in the tourism industry. Chapter 11 critically analyzes the use of business coaching as a leadership development tool for tourism operators in regional destinations.